Tashmim Al’ab Lughawiyah Li Ta’limi Al-Lughah Al-‘Arabiyah Lil Mubtadiin Min Khilal Al-Kalimati Al-Minangkabawiyah Dzati Aslin ‘Arabi Fii Qomus ( Bahasa Indonesia – Minangkabau ) Min Harfi “ A “ ILA “ M “ - Anggi Maulana; Hadil Ismail (Mauriduna: Journal of Islamic Studies, 2020)
هدفت هذه الدراسة إلى اكتشاف الكلمات المينانجكابوية ذات أصل عربي في قاموس ( Bahasa Indonesia - Minangkabau ) من حرف " A " إلى " M ", وهدفت هذه الدراسة إلى معرفة تغير معنى الكلمات العربية بعد دخولها في اللغة المينانجكابوية, وهدفت إلى كيفية تصميم ألعاب اللغوية من تلك الكلمات لمساعدة المبتدئين في تعليم اللغة العربية.إن هذه الدراسات تدخل من ضمن البحث النوعي ويسمى كذلك بالمنهج الكيفي والمنهج الوصفي, واستخدم الباحث المنهج الوصفي التحليلي في كتابة هذه الدراسة. وأثبت الباحث منها بوجود الكلمات المينانجكابوية ذات أصل عربي في قاموس ( Bahasa Indonesia - Minangkabau ) من حرف " A " إلى " M " وبلغ عددها مئة خمسة وستين ( 165 )كلمة. وتواصل الباحث إلى وجود التغيرات في الكلمات العربية بعد دخولها في اللغة المينانجكابوية إلى أربعة أقسام كما يتواصل الباحث إلى طرق تصميم ألعاب اللغوية من تلك الكلمات على حسب المهارات الأربع لمساعدة المبتدئين في تعليم اللغة العربية. The purpose of this study is to point out absorbed Minangkabau Words from Arabic in “ Bahasa Indonesia – Minangkabau “ dictionary from the “ A “ to “ M “, and to know meaning’s change from each words in Minangkabau language, and also the aim from this study is how to design language games from these words to help first grade students in their study for Arabic. This study is including in qualitative research and are also called qualitative and descriptive method. To write this study research used the descriptive analitycal method. And this study has proved absorbed Minangkabau words from arabic in ( Bahasa Indonesia – Minangkabau ) Dictionary from “ A “ to “ M “ and the number of these words is one hundred and sixty five ( 165 ) words. And the reseach found meaning’s change when the words are absorbed from arabic to Minangkabau language, and these changes are in four types. And the research found methods of designing language games from these words to help first grade students in their study for Arabic, and these method are in the four language skills.